Formal auditory training in adult hearing aid users - Daniela Gil; Maria Cecília Martinelli Iorio (Clinics, 2010)
INTRODUCTION: Individuals with sensorineural hearing loss are often able to regain some lost auditory function with the help of hearing aids. However, hearing aids are not able to overcome auditory distortions such as impaired frequency resolution and speech understanding in noisy environments. The coexistence of peripheral hearing loss and a central auditory deficit may contribute to patient dissatisfaction with amplification, even when audiological tests indicate nearly normal hearing thresholds. OBJECTIVE: This study was designed to validate the effects of a formal auditory training program in adult hearing aid users with mild to moderate sensorineural hearing loss. METHODS: Fourteen bilateral hearing aid users were divided into two groups: seven who received auditory training and seven who did not. The training program was designed to improve auditory closure, figure-to-ground for verbal and nonverbal sounds and temporal processing (frequency and duration of sounds). Pre- and post-training evaluations included measuring electrophysiological and behavioral auditory processing and administration of the Abbreviated Profile of Hearing Aid Benefit (APHAB) self-report scale. RESULTS: The post-training evaluation of the experimental group demonstrated a statistically significant reduction in P3 latency, improved performance in some of the behavioral auditory processing tests and higher hearing aid benefit in noisy situations (p-value < 0,05). No changes were noted for the control group (p-value <0,05). CONCLUSION: The results demonstrated that auditory training in adult hearing aid users can lead to a reduction in P3 latency, improvements in sound localization, memory for nonverbal sounds in sequence, auditory closure, figure-to-ground for verbal sounds and greater benefits in reverberant and noisy environments.